Trabecular bone score and phalangeal quantitative ultrasound are associated with muscle strength and fracture risk in hemodialysis patients - Catalano, Antonino; Gaudio, Agostino; Bellone, Federica; La Fauci, Mattia Miriam; Xourafa, Anastasia; Gembillo, Guido; Basile, Giorgio; Natale, Giuseppe; Squadrito, Giovanni; Corica, Francesco; Morabito, Nunziata; Santoro, Domenico (Frontiers in Endocrinology, 2022)
There is growing interest in the relationship between chronic kidney disease (CKD) and fragility fracture risk. The bone mineral density (BMD) is a major determinant of bone strength, although its role as a predictor of fracture in advanced CKD and hemodialysis is still under debate. We aimed to further investigate surrogates of bone quality and their associations with muscle strength and fracture risk in hemodialysis. Multiple clinical risk factors for fracture and estimated 10-year probability of fracture, BMD at lumbar spine and femur, Trabecular Bone Score (TBS), X-ray vertebral morphometry, phalangeal bone Quantitative UltraSonography (QUS), tibial Pulse-Echo UltraSonography (PEUS) and handgrip strength were evaluated in a setting of hemodialysis patients in treatment with Acetate Free Biofiltration (AFB) or Bicarbonate Hemodialysis. The bone ultrasound measurements, both at phalangeal and tibial sites, were significantly associated with lumbar and femoral DXA values. Handgrip strength was significantly associated with the 10-year probability of fracture (r=-0.57, p<0.001 for major fractures and r=-0.53, p<0.001 for hip fracture, respectively), with femur neck, total femur and L1-L4 BMD values (r=0.47, p=0.04; r=0.48, p=0.02; r=0.58, p=0.007, respectively), with TBS at lumbar spine (r=0.71, p<0.001) and with the phalangeal QUS measure of AD-SoS (r=0.369, p=0.023). In the hemodialysis group, 10 participants (24.3%) reported at least one morphometric vertebral fracture (Vfx); conversely, only 6 participants (15%) showed Vfx in the control group. In the hemodialysis group, participants with Vfx compared with participants without Vfx reported significantly different TBS, bone transmission time (BTT), cortical thickness and handgrip strength (p<0.05). At multiple regression analysis, by identifying as dependent variable the 10-year fracture risk for major fracture, after correcting for age, BMI, time since dialysis, AD-SoS, cortical bone thickness and handgrip strength, only BTT (β= -15.21, SE= 5.91, p=0.02) and TBS (β= -54.69, SE= 21.88, p=0.02) turned out as independently associated with fracture risk. In conclusion, hemodialysis patients showed a higher fracture risk and lower surrogate indices of bone strength as TBS and QUS parameters. In this cohort of patients, handgrip strength measurements appeared to be a useful instrument to identify high-fracture-risk subjects.